Risk Assessment of Air Pollution by Using Fuzzy Process Incapability Index with Asymmetric Tolerances - Kaya, Ihsan; Kahraman, Cengiz (ATLANTIS PRESS, 2011)
Air pollution is one of the most important threats that damage people, environment, animal and the other component of natural life. Therefore a number of effective techniques have been proposed to suggest new solutions to prevent air pollution's damage effects. In this paper a new approach based on process capability index is proposed under fuzzy environment which is used to obtain a deep and flexible analysis. For this aim, classical process incapability index with asymmetric tolerances (C ''(pp)) is analyzed to produce fuzzy process incapability index with asymmetric tolerances ((C) over tilde ''(pp)) bused on fuzzy process mean ((mu) over tilde), fuzzy variance ((sigma) over tilde (2)), fuzzy specification limits (S (L) over tildes) and fuzzy target value ((T) over tilde). Then the indices (C) over tilde ''(pp) for two main air pollutants that are SO2 and PM10 are obtained the case of Istanbul, Turkey.
Keywords: Air pollution; process incapability index; fuzzy set theory; risk assessment; Computer Science; Science & Technology - Other Topics